Embryonal rhabdomyosarcoma masquerading as a left vocal cord granuloma. Issue 10 (30th October 2020) - Linton, Stefan; Stapleton, Emma; Penney, Susannah; Sharma, Manu-Priya
Abstract : Embryonal rhabdomyosarcoma (ERMS) of the larynx in adults is an extremely rare diagnosis with insidious onset and progression. Only six reports (including this one) have been documented in the literature. Clinical presentation is dependent on the site, size, subtype of ERMS and growth rate. Hoarseness is the usual first symptom, followed by stridor and dyspnoea, with dysphagia being late in onset. Accurate staging and risk stratification is necessary to avoid overtreating/undertreating patients and should be guided by local Head and Neck/Sarcoma Multidisciplinary Teams. Treatment has moved away from radical therapeutic regimens to less-invasive, organ-preserving therapies. Long-term follow-up is required due to the risk of late recurrence.